Respuesta :

Answer:

9/-6

Step-by-step explanation:

when you subtract (x2-x1) and (y2-y1) this is the answer you get.

Answer:

[tex]-\frac{3}{2}[/tex]

Step-by-step explanation:

Use the point slope formula

[tex]Slope = m = \frac{y_2-y_1}{x_2-x_1} = \frac{13-4}{-2-(-8)} = \frac{9}{6} = \frac{9}{6} = \frac{3}{2}[/tex]

This is the difference between two points with the rise (change in y) over the run (change in x)

Sorry it took so long for so little my girlfriend was distracting me

Hope this helps :)